Characterization of Brazilian Industrial Companies’ Processes and Challenges as to Innovation Management - Nagano, Marcelo Seido; Stefanovitz, Juliano Pavanelli; Vick, Thais Elaine (Review of Business Management, 2014)
The goal of this study is to investigate the use of product innovation management practices and the challenges faced by organizations when increasing their innovative performance. To this end, we analyzed the relationships between internal organizational elements, as well as the influence of contextual factors (size, field and source of capital) in the characterization of innovation management systems and of barriers to innovation faced by each company. We chose this topic due to the fact that management processes that leverage innovative performance are not yet fully understood, and because of the lack of empirical studies that analyze the reality of the practices proposed in the organizational world, especially in Brazil. As a conceptual basis, we presented modern approaches to innovation, which recognize that this should not be seen as an isolated event but as a process. Exploratory qualitative research was carried out by means of a multiple case study. In it, we studied the innovation management systems of four companies which present relevant product development activities in Brazil. As well as a detailed study of the elements of innovation management, this article includes contributions referring to the characterization of organizational challenges faced by organizations when managing their innovation process.